2016
DOI: 10.1175/jas-d-15-0212.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Eddy Momentum Fluxes in Determining the Characteristics of the Equinoctial Hadley Circulation: Fixed-SST Simulations

Abstract: The influence of eddy momentum fluxes on the equinoctial Hadley circulation is explored using idealized simulations on an equatorial beta plane in which the sea surface temperature (SST) distribution is fixed. By comparing simulations run in a wide-domain configuration, in which large-scale eddies are present, to simulations in which the model domain is too narrow to permit baroclinic instability, the role of large-scale eddies in determining the characteristics of the Hadley circulation is elucidated. The sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…A more realistic control run could be obtained by prescribing additional eddy momentum (or heat) forcing in the mid-latitudes (Schneider, 1984;Singh and Kuang, 2016), as was done in Caballero and Carlson (2018). For simplicity, we prefer not to do so here.…”
Section: B Control Runmentioning
confidence: 99%
“…A more realistic control run could be obtained by prescribing additional eddy momentum (or heat) forcing in the mid-latitudes (Schneider, 1984;Singh and Kuang, 2016), as was done in Caballero and Carlson (2018). For simplicity, we prefer not to do so here.…”
Section: B Control Runmentioning
confidence: 99%
“…On Earth, baroclinic eddies modulate the Hadley cells' extent and overturning strength (e.g. Walker and Schneider 2005;Korty and Schneider 2008;Levine and Schneider 2015;Singh and Kuang 2016;Singh et al 2017) and decelerate the zonal wind of the annual mean Hadley cells well below the AMC limit (Held and Hoskins 1985;Walker and Schneider 2006). Nevertheless, large expanses of crossequatorial, zonally confined monsoons and zonal mean Hadley cells during solsticial seasons do approximately behave as in the AMC regime, with local Rossby numbers Ro ≡ −ζ/ f ∼ 0.6 compared to Ro = 1 for the true AMC solution and Ro = 0 for the purely eddy-dominated case (e.g.…”
Section: Caveatsmentioning
confidence: 99%
“…This widening tendency is in qualitative agreement with Sobel and Neelin (2006), who found that increasing the horizontal moisture diffusivity in an axisymmetric model (analogous to increasing the transient-eddy moisture flux) resulted in a wider ITCZ. Transient eddies have previously been shown to modulate the strength of the Hadley circulation through their effect on the both the angular momentum and energy budgets (Singh and Kuang 2016) of the tropics, and are also important for the extent of the Hadley circulation (Korty and Schneider 2008;Levine and Schneider 2015). Although MSE divergence by transient eddies has been found to be an important term in the energy budgets of the eastern Pacific (Peters et al 2008) and the ITCZ in an idealized model (Nolan et al 2010), the quantitative relationship between transient eddies and the size of the ITCZ has not been demonstrated previously.…”
Section: ) Transient-eddy Component Deddymentioning
confidence: 99%